1991
DOI: 10.1128/mcb.11.7.3515
|View full text |Cite
|
Sign up to set email alerts
|

The block to transcription elongation at the minute virus of mice attenuator is regulated by cellular elongation factors.

Abstract: We have previously reported that both in vivo and in vitro, RNA polymerase H pauses or prematurely terminates transcription at a specific attenuation site located 142 to 147 nucleotides downstream from the P4 promoter of minute virus of mice (MVM). In this report, we show that an in vitro block to transcription elongation in HeLa whole-cell extract occurs at elevated KCI concentrations (0.2 to 1.5 M) but not at the standard KCI concentration (50 mM). Briefly initiated transcription complexes, devoid of dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The reason runoff in the presence of high Sarkosyl did not return to the level in the untreated reactions is that reinitiation is inhibited above 0.025% Sarkosyl (26). Other investigators working on attenuation in synthetic and natural virus sequences have found stimulations with elevated concentration of KCI (6,38). Sarkosyl and heparin have been used to inhibit reinitiation by many investigators (1, 6, 31 (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason runoff in the presence of high Sarkosyl did not return to the level in the untreated reactions is that reinitiation is inhibited above 0.025% Sarkosyl (26). Other investigators working on attenuation in synthetic and natural virus sequences have found stimulations with elevated concentration of KCI (6,38). Sarkosyl and heparin have been used to inhibit reinitiation by many investigators (1, 6, 31 (31).…”
Section: Discussionmentioning
confidence: 99%
“…The second factor, factor 5 from D. melanogaster (or mammalian TFIFF or RAP 30/74), is required for initiation and also stimulates the elongation rate of RNA polymerase II (5,9,19,56,57). The third factor, TFIIX, was identified in HeLa cell extract and stimulates elongation by RNA polymerase 11 (5,38). Finally, a recently identified yeast protein, YES, stimulates the elongation rate of RNA polymerase II (12).…”
mentioning
confidence: 99%
“…The extent of the elongation block correlates with the stability of the RNA hairpin and the length of the T stretch in the DNA (7). Regulation of attenuation at these sites in vivo might be effected through changes in the abundance of elongation factors (like transcription factor IIS) or in their interaction with the transcribing polymerases on the genes with attenuation signals (9,28). RNA pol I from Saccharomyces cerevisiae also terminates in a T-rich region coding for the last 12 nucleotides of the transcript (30).…”
mentioning
confidence: 99%
“…Upon dilution or removal of the disruptive agent by gel filtration, exogenously added SII was able to promote read-through of intron 1 arrested complexes (26). Others have used similar approaches, including high-salt washes of immobilized templates, to study the elongation factors themselves (4,5,25,32). A second and very different effect of the increased postinitiation KCl concentrations was an increase in the overall levels of transcription from the ADA promoter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes from Drosophila melanogaster as well, including the heat shock genes hsp70 and hsp26, show regulation at the level of transcription elongation (35,44,51). Viral transcription units also show this type of control, including those of human immunodeficiency virus (46, 54), adenovirus (42, 49, 56), polyomavirus (53), and the minute virus of mice (2,32,48). The diversity among these examples may indicate that control of transcription elongation is a widespread gene regulatory phenomenon.…”
mentioning
confidence: 99%